Duplex Sonographic Evaluation of Hepatic Vasculature in Cirrhosis - Ahmad, K; Khanna, SK; Sundas, A; Rauniyar, RK; Koirala, R; Gupta, MK (Nepal Journal of Medical Sciences, 2013)
Background: Cirrhosis of liver in an ancient illness, known to the mankind since antiquity. Alcohol consumption is the most important cause of micronodular cirrhosis and chronic hepatitis is the most frequent cause of macronodular cirrhosis. The objective of this study was to assess the morphological changes and flow haemodynamics in portal vein, hepatic vein and hepatic artery using various Doppler parameters. Methods: The study was done on prospective basis in 35 patients with clinical diagnosis of cirrhosis and these patients were subjected to ultrasonography of the abdomen for the assessment of morphological changes and flow haemodynamics in hepatic vasculature. Results: Portal venous blood flow becomes reversed with advanced portal hypertension, veno-occlusive disease and portosystemic shunts. Reduced portal blood flow velocity was observed in majority of the patients and was found to be lower in patients with history of variceal haemorrhage. Hepatic artery resistive index was found to be significantly higher in patients with dilated coronary veins as compared to those with normal non-dilated veins. Dilated paraumbilical vein was the most consistently observed collateral followed by dilated coronary veins. Abnormal hepatic vein flow profiles are seen in patients with cirrhosis, with decreased amplitude of phasic occilation pattern being the most frequently observed abnormality. Conclusion: Although many factors may affect the accuracy of volume flow and velocity measurements and the flow profile of the liver vasculature may change in different situations, Doppler ultrasound is useful in the assessment of the patient with cirrhosis and portal hypertension. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 13-19 DOI: http://dx.doi.org/10.3126/njms.v2i1.7645